Nutritional and health status of children 15 months after integrated school garden, nutrition, and water, sanitation and hygiene interventions: a cluster-randomised controlled trial in Nepal - Akina Shrestha; Christian Schindler; Peter Odermatt; Jana Gerold; Séverine Erismann; Subodh Sharma; Rajendra Koju; Jürg Utzinger; Guéladio Cissé (BMC, 2020)
Abstract Background It has been suggested that specific interventions delivered through the education sector in low- and middle-income countries might improve children's health and wellbeing. This cluster-randomised controlled trial aimed to evaluate the effects of a school garden programme and complementary nutrition, and water, sanitation and hygiene (WASH) interventions on children's health and nutritional status in two districts of Nepal. Methods The trial included 682 children aged 8-17 years from 12 schools. The schools were randomly allocated to one of three interventions: (a) school garden programme (SG; 4 schools, n = 172 children); (b) school garden programme with complementary WASH, health and nutrition interventions (SG+; 4 schools, n = 197 children); and (c) no specific intervention (control; 4 schools, n = 313 children). The same field and laboratory procedures were employed at the baseline (March 2015) and end-line (June 2016) surveys. Questionnaires were administered to evaluate WASH conditions at schools and households. Water quality was assessed using a Delagua kit. Dietary intake was determined using food frequency and 24-h recall questionnaire. Haemoglobin levels were measured using HemoCue digital device and used as a proxy for anaemia. Stool samples were subjected to a suite of copro-microscopic diagnostic methods for detection of intestinal protozoa and helminths. The changes in key indicators between the baseline and end-line surveys were analysed by mixed logistic and linear regression models. Results Stunting was slightly lowered in SG+ (19.9 to 18.3%; p = 0.92) and in the control (19.7 to 18.9%). Anaemia slightly decreased in SG+ (33.0 to 32.0%; p < 0.01) and markedly increased in the control (22.7 to 41.3%; p < 0.01), a minor decline was found in the control (43.9 to 42.4%). Handwashing with soap before eating strongly increased in SG+ (from 74.1 to 96.9%; p = 0.01, compared to control where only a slight increase was observed from 78.0 to 84.0%). A similar observation was made for handwashing after defecation (increase from 77.2 to 99.0% in SG+ versus 78.0 to 91.9% in control, p = 0.15). Conclusions An integrated intervention consisting of school garden, WASH, nutrition and health components (SG+) increased children's fruit and vegetable consumption, decreased intestinal parasitic infections and improved hygiene behaviours. Trial registration ISRCTN17968589 (date assigned: 17 July 2015).